Review Essay on Why Muslim Integration Fails in Christian-Heritage Societies by Claire Adida, David Laitin and Marie-Anne Valfort - Verdier, Thierry (Journal of Economic Literature, 2019)
This paper reviews the book Why Muslim Integration Fails in Christian-Heritage Societies by Claire Adida, David Laitin and Marie-Anne Valfort (hereafter, ALV), providing an analytical perspective on the issues related to minority discrimination and integration in a host society. Building upon the sociological and recent economic approaches to cultural integration, we highlight the different mechanisms behind the existence of a discriminatory equilibrium between a majority group and a minority group in a given social context. The paper then discusses the specific case of the Muslim minority groups in the French context and outlines the strengths and limitations of the research approach expanded by ALV. We finally consider the policy proposals provided by ALV, assessing their viability, as well as the dynamic political economy constraints they might face in a Christian-heritage society. (JEL J15, Z12, Z13)